2023
DOI: 10.1038/s41467-023-38787-w
|View full text |Cite
|
Sign up to set email alerts
|

Imaging quantized vortex rings in superfluid helium to evaluate quantum dissipation

Abstract: The motion of quantized vortices is responsible for many intriguing phenomena in diverse quantum-fluid systems. Having a theoretical model to reliably predict the vortex motion therefore promises a broad significance. But a grand challenge in developing such a model is to evaluate the dissipative force caused by thermal quasiparticles in the quantum fluids scattering off the vortex cores. Various models have been proposed, but it remains unclear which model describes reality due to the lack of comparative expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, direct experimental observations of the predicted effect have been absent up to now, and theoretical calculations of different groups have given different prognoses concerning the exact mechanism and the magnitude of dissipation. Y Tang (National High Magnetic Field Laboratory and Florida State University, USA) and her co-authors have performed a new experiment, where the dissipation effect in vortices was observed for the first time [4]. To this end, solid deuterium particles were added to liquid helium-4 as markers.…”
Section: Dissipation In Superfluid Vortex Ringsmentioning
confidence: 99%
“…However, direct experimental observations of the predicted effect have been absent up to now, and theoretical calculations of different groups have given different prognoses concerning the exact mechanism and the magnitude of dissipation. Y Tang (National High Magnetic Field Laboratory and Florida State University, USA) and her co-authors have performed a new experiment, where the dissipation effect in vortices was observed for the first time [4]. To this end, solid deuterium particles were added to liquid helium-4 as markers.…”
Section: Dissipation In Superfluid Vortex Ringsmentioning
confidence: 99%